Методи визначення часткового внеску суб'єктів у погіршенні показників якості електроенергії - Гриб, Олег Герасимович; Щербакова, Поліна Геннадіївна (Донецький національний технічний університет, 2008)
Techniques of definition of the share contribution of consumers and suppliers in distortion of the established deviation of a voltage, symmetry and sinusoidally are proved and developed. The complex technique of an estimation of the partial contribution of subjects in infringement of quality of the electric power is developed.
Keywords: енергозбереження; показник якості; напруга; симетрія